ANALISIS SEMIOTIKA KRITIK SOSIAL MASYARAKAT MODERN DALAM VIDEO KLIP “ANTI SOCIAL” OLEH WHILE SHE SLEEPS - Alvin Tito Anggoro; Fitria Widiyani Roosinda (Universitas Tribhuwana Tunggadewi, 2020)
Abstract : Music is used as a medium to convey social, political aspirations, and even becomes one of propaganda media (information / opinions) to launch an ideological movement (ideas / ideas). Song lyrics are one of the verbal communication media that have meaning in them. Research on the video clips and song lyrics of the band while she sleeps